2008
DOI: 10.1002/jcp.21389
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐2 regulation of PTHrP and osteoclastogenic factors during osteoblast differentiation of C2C12 cells

Abstract: Bone morphogenetic protein-2 (BMP-2) is strongly involved in the induction of osteoblast differentiation from mesenchymal cell precursors, as well as in enhancing bone matrix production by osteoblastic cells. Likewise, the osteoporotic phenotype of PTHrP deficient mice makes clear the importance of this paracrine regulator in bone physiology. Here, we report that BMP-2 rapidly down-regulated PTHrP gene expression through a transcriptional mechanism in pluripotent mesenchymal C2C12 cells, whereas BMP-2 increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 53 publications
(66 reference statements)
0
31
1
Order By: Relevance
“…As discussed earlier, muscle progenitor cells exposed to appropriate cues are permissive to committing toward an osteogenic lineage. It is known that BMP can induce an osteoblast phenotype even in the C2C12 model used in our studies (125)(126)(127)(128)(129)(130)(131)(132). Moreover, we have also recently reported that down-regulation of the Men-1 gene product (Menin) is a prerequisite to myogenesis, and maintenance of its expression favors osteoblast, rather than myoblast, commitment in multipotent mesenchymal cells such as C2C12 and C3H10T1/2 cell lines (106).…”
Section: Discussionmentioning
confidence: 63%
“…As discussed earlier, muscle progenitor cells exposed to appropriate cues are permissive to committing toward an osteogenic lineage. It is known that BMP can induce an osteoblast phenotype even in the C2C12 model used in our studies (125)(126)(127)(128)(129)(130)(131)(132). Moreover, we have also recently reported that down-regulation of the Men-1 gene product (Menin) is a prerequisite to myogenesis, and maintenance of its expression favors osteoblast, rather than myoblast, commitment in multipotent mesenchymal cells such as C2C12 and C3H10T1/2 cell lines (106).…”
Section: Discussionmentioning
confidence: 63%
“…Osteoblasts secrete PTHrP and express its receptor , and increasing evidence suggests that PTHrP may be an important local regulator of mesenchymal cell commitment and osteoblast activity (Chan et al, 2003;Martin, 2005;Goltzman, 2008). The effects of PTHrP on osteoblasts in vitro are known to vary with the culture conditions (Isogai et al, 1996;Ishizuya et al, 1997), but the majority of studies have shown that continuous exposure to PTHrP inhibits osteoblastic differentiation, although this may be mediated by PKA (Isogai et al, 1996;Susperregui et al, 2008), PKC (Miao et al, 2001), or both pathways (Ishizuya et al, 1997). In the present study PTHrP strongly suppressed ALP activity in osteoblasts, while PKA pathway activation slightly suppressed it, suggesting that PTHrP induces additional pathways to regulate ALP activity.…”
Section: Discussionmentioning
confidence: 98%
“…Under normal circumstances, pluripotent muscle-derived C2C12 cells develop and differentiate into muscle cells, however treatment with BMP-2 causes them to differentiate into osteoblasts (36). Thus, C2C12 cells have been widely used to study osteoblast differentiation in early stage.…”
Section: Discussionmentioning
confidence: 99%